The practice of mediation as a mechanism of family dispute resolution: a comparative analysis between Malaysia and Indonesia - Mohd Alam Shah, Nurin Athirah; Drs Nasrul, Muhammad Amrullah; Abd Rahman, Siti Fatimah; Seviyana, Devi (2023)
Mediation is one of the Alternative Dispute Resolution (ADR) that emphasises a mutually agreeable resolution technique and incorporates elements of soft dispute resolution namely win-win situation. Mediation allows the parties involved in a dispute to participate by outlining their solutions. History suggests that mediation has been practiced in Malaysia a long time ago, despite not incorporating all features of mediation. The same practice takes place in Indonesia where mediation is one of the preferred methods of dispute resolution in Indonesia. Hence, mediation is not a rare concept in Malaysia and Indonesia due to their long existence and constant practice in Alternative Dispute Resolution (ADR). To this date, mediation has grown in popularity as a form of Alternative Dispute Resolution (ADR) in both countries an even being used as an alternative compared to litigation. In this paper, it will review the practice of mediation in Malaysia and Indonesia via a comparison analysis. This research employs a qualitative approach. In understanding the phenomenon more thoroughly, an exploratory research design is adopted by using the secondary research method which is the analysis of the data. The result of this study affirms that mediation practices in Malaysia and Indonesia are quite similar, despite being governed under a different perspectives. The differences can be found in a number of areas namely legislation of mediation, qualification and status of a mediator, matters outside the scope of mediation, conduct of mediation, cost of mediation, existence of restorative justice and lastly application of mediation customary practice. Although mediation has been established in both countries and bring many benefits and goodness to both countries, there are still challenges that need to be overcome related to mediation especially regarding lack awareness among the society and lack of legislation regarding mediation especially pertaining family disputes. Therefore, with this research, the author hopes that the recommendations given can solve both of these challenges and at the same time the author hoped that this research can be used as a complete guidebook to make a comparative analysis between Malaysia and Indonesia in related to the practice of mediation, especially related to family disputes.